Wolność zrzeszania się obywateli według prawa o stowarzyszeniach z 1989 r. - Wiśniewski, Leszek (Digitalizacja i deponowanie archiwalnych zeszytów RPEiS sfinansowane przez MNiSW w ramach realizacji umowy nr 541/P-DUN/2016, 1990)
The article discusses four problems: political conditions existing at a time of the adoption of a new Law on Associations; types of associations regulated by the Law; the notion of freedom of association in the light of the Law and the consistence of the Polish Law with International Covenant on Citizens' and Political Rights. The author states that the Law on Associations of 1989 is the element of deep changes in the political system of the State. It reflects the demands of the society, which has since long formulated the postulates of widening the scope of political rights or liberties, especially with respect to freedom of association in trade unions, associations and political parties. In a larger part of his article the author considers the question whether the Law on Associations of 1989 is applicable also to political parties. This problem is analysed in the context of praxis, the provisions of the Law of 1989 and the Constitution. A considerable part of considerations concerns the notion of freedom of association and solutions adopted by the Law of 1989. The author concludes that the new Law is consistent with the principle of citizens freedom of association. The expression of that principle is found in guaranties of freedom to form associations, freedom to acquire and give up membership in associations and members' freedom to determine the aims and programmes of activity of associations. In the last part of his article the author states that the Law on Associations of 1989 is consistent with the requirements of international law determined in the International Covenant on Citizens' and Political Rights.
Freedom of association according to the law on association of 1989